A Study On SMS Reminders And Their Impact On Customer Service Improvement In Malaysia - Mok, Meng Hua (2008)
The major objective of this research is to ascertain whether the use of SMS-based reminders can improve customer service. The specific objectives which may assist in achieving this major objective will be reviewed and generated by literature review and research methodology.